2005
DOI: 10.1002/syn.20166
|View full text |Cite
|
Sign up to set email alerts
|

Learning and memory after neonatal exposure to 3,4‐methylenedioxymethamphetamine (ecstasy) in rats: Interaction with exposure in adulthood

Abstract: This study determined whether developmental and adult 3,4-methylenedioxymethamphetamine (MDMA) exposures in rats have interactive effects on body temperature, learning, other behaviors, and monoamine concentrations in the hippocampus, prefrontal cortex, and striatum. Learning was assessed in the Cincinnati water maze (CWM), Morris water maze (MWM), and novel object recognition (NOR). On acquisition trials in the MWM, significant differences from developmental MDMA exposure were found on latency, cumulative dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 49 publications
7
59
1
Order By: Relevance
“…All tests were performed during the light phase of the light/dark cycle. This order of testing closely follows one that we have used to assess the impact of a single day exposure to other psychostimulants in adult animals (Cohen et al, 2005;Skelton et al, 2004;Williams et al, 2002). We have previously shown that the order of the CWM and MWM does not significantly affect the outcome with these compounds (Williams et al, 2002).…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…All tests were performed during the light phase of the light/dark cycle. This order of testing closely follows one that we have used to assess the impact of a single day exposure to other psychostimulants in adult animals (Cohen et al, 2005;Skelton et al, 2004;Williams et al, 2002). We have previously shown that the order of the CWM and MWM does not significantly affect the outcome with these compounds (Williams et al, 2002).…”
Section: Methodsmentioning
confidence: 77%
“…5-MEO-DIPT or SAL was administered four times at 2-h intervals on a single day (ie, the entire dosing period was 6 h from first to last dose). The multiple dose regimen is consistent with drug administration paradigms for other psychostimulants (Cappon et al, 1997;Cohen et al, 2005;Farfel and Seiden, 1995;O'Callaghan and Miller, 2002;O'Dell and Marshall, 2002). Injections were applied subcutaneously in the dorsum and the injection sites were varied to prevent irritation to the dermis, although some minor irritation was observed.…”
Section: -Meo-dipt Administrationmentioning
confidence: 85%
See 1 more Smart Citation
“…Periadolescent MDMA treatments diminished the time spent exploring the objects, a gross index of attentional behavior [118], and decreased the discrimination ratio in this paradigm [119]. Neonatal MDMA (PD 11-20) diminished water maze learning and novel object exploration in adult-rats [27]. However, MDMA administration at earlier postnatal periods did not alter these endpoints [11,120].…”
Section: Learning and Memorymentioning
confidence: 93%
“…The behavioral effects of MDMA (Table 2) are not limited to the period immediately after drug exposure as changes have also been documented weeks to months after MDMA [16,17,[24][25][26][27]92,93,118,119,155,159,166,168].…”
Section: Long-term Behavioral Consequencesmentioning
confidence: 99%